P-98 Patient and caregiver experiences of do not attempt cardiopulmonary resuscitation (DNACPR) conversations: an integrative review of the literature. (1st March 2017) - Carduff, Emma; Lugton, Jean; Spiller, Juliet; Hall, Charlie
Abstract : Background: Following recent changes in UK case law, DNACPR decisions must be discussed with patients unless that conversation will cause harm. CPR should not be given if it is an inappropriate treatment. DNACPR conversations are therefore happening more frequently; yet evidence to support staff in knowing how to undertake these conversations is scarce from the patient/caregiver perspective. This integrative literature review aims to identify patient and family experiences of DNACPR conversations. Methods: A search of multiple databases was performed for adult patients and caregivers, from all settings worldwide (2004–2014). Abstracts were reviewed for relevance and quality. First person, retrospective accounts of patient/carer experience of DNACPR conversations were gold standard. Relevant full texts were appraised and recurring themes analysed and tabulated. Results: The initial search identified 559 abstracts. Of these, 46 full texts were deemed relevant including 9 UK and 37 international papers. Only 22 papers were original research with patients or carers who had experienced these conversations. Themes revealed the importance of DNACPR discussions being conducted by someone trusted and the importance of family/carer involvement, as well as perceived concerns about burdening family members. Timing preferences for discussions was variable revealing difficulties in finding the 'right time' to discuss. Discussions held at home or the GP surgery are preferable to discussions during acute admissions to hospital. Conclusions: This review highlights potential discrepancies between patient and carer preferences for DNACPR conversations, and the reality of how these conversations are currently taking place. Public health approaches to tackle the societal taboo around death and dying may encourage people to think about and expect such conversations during their illness trajectories. Discussion of DNACPR decisions with the patient is now a legal requirement, but patient centred care remains paramount. More evidence is essential to bridge these expectations.